Attenuation of Dictyocaulus filaria larvae by visible Laser radiation : 2- In vivo study - AL-S amarrae, S. A. G; AL- Mishhadani, F. J. K. (The Iraqi Journal of Veterinary Medicine, 2000)
Attenuated 3rd stage larvae of Dictyocaulus filaria, by continuos emission of visible Helium- Neon laser of 1mW and a wave length of 632.8 nm for 2.5,5,10 and 15 minutes, were dosed twice orally to four groups of five kids each. The first dose contained 1000 larvae and after five weeks a second dose of 2000 larvae was given . A 5 th group of five kids was left as control. Results showed that attenuation at 2.5 min. exposure was insufficient as indicated by the increase in respiratory rate, eosinophilia and shading of larvae in the feaces. The results indicated that attenuation of Dictyocaulus filaria larvae at (5, 10 , and 15) min. exposure to laser radiation were efficient and safe to be used as attenuated vaccine .